A randomized controlled trial of 24 weeks of varenicline for tobacco use among cancer patients: Efficacy, safety, and adherence. Issue 3 (24th January 2019) - Schnoll, Robert; Leone, Frank; Veluz‐Wilkins, Anna; Miele, Andrew; Hole, Anita; Jao, Nancy C.; Paul Wileyto, E.; Carroll, Allison J.; Kalhan, Ravi; Patel, Jyoti; Langer, Corey; Lubitz, Su Fen; et al.
Abstract: Objective: Continuing to smoke after a cancer diagnosis undermines prognosis. Yet few trials have tested Food and Drug Administration (FDA)‐approved tobacco use medications in this population. Extended use varenicline may represent an effective treatment for cancer patients who smoke given barriers to cessation including a prolonged time line for relapse. Methods: A placebo‐controlled randomized trial tested 12 weeks of varenicline plus 12 weeks of placebo (standard [ST]) vs 24 weeks of varenicline (extended [ET]) with seven counseling sessions for treatment‐seeking cancer patients who smoke (N = 207). Primary outcomes were 7‐day biochemically confirmed abstinence at weeks 24 and 52. Treatment adherence and side effects, adverse and serious adverse events, and blood pressure were assessed. Results: Point prevalence and continuous abstinence quit rates at weeks 24 and 52 were not significantly different across treatment arms ( P 's > 0.05). Adherence (43% of sample) significantly interacted with treatment arm for week 24 point prevalence (odds ratio [OR] = 2.31; 95% confidence interval [CI], 1.15‐4.63; P = 0.02) and continuous (OR = 5.82; 95% CI, 2.66‐12.71; P < 0.001) abstinence. For both outcomes, adherent participants who received ET reported higher abstinence (60.5% and 44.2%) vs ST (44.7% and 27.7%), but differences in quit rates between arms were not significant for nonadherent participants (ET: 9.7% and 4.8%; ST: 12.7% and 10.9%). There were no significant differences between treatment arms on side effects, adverse and serious adverse events, and rates of high blood pressure ( P 's > 0.05). Conclusions: Compared with ST, ET varenicline does not increase patient risk and increases smoking cessation rates among patients who adhere to treatment. Studies are needed to identify effective methods to increase medication adherence to treat patient tobacco use effectively.